Potensi Kompos Cotayam Sebagai Pupuk Organik Pada Budidaya Melon Sebagai Bahan Penyusunan Modul Ajar Kurikulum Merdeka - Alam, Tago; Muhfahroyin; Sutanto, Agus; Widowati, *Hening (BIOLOVA, 2024)
Cultivating melons with organic fertilizer is an agricultural technique that uses natural ingredients to increase soil fertility and plant health. This method is not only environmentally friendly, but is also able to produce healthier and tastier melons. This literature review aims to explore the potential of cocopeat waste, shrimp pond sediment and chicken waste as organic fertilizer in melon cultivation as material for preparing modules in the independent curriculum. These three types of waste contain high nutrients and have the potential to be used as organic fertilizer. Research that has been conducted shows that this organic fertilizer can increase plant growth and yields, as well as reduce the use of chemical fertilizers. Integrating the cotayam compost application into biology learning can increase scientific literacy, as well as awareness of environmental impacts and sustainability.